Child’s creativity friendly home environmental status among students in uyo senatorial districts, Akwa Ibom State (2023)
The study assessed the child creativity-friendly home environmental (CCFHE) status in Uyo senatorial district due to the sensitivity of the construct variable transformative development of the social and economic wellbeing of the individual and the economy. The background characteristics of the respondents were identified, the child's creativity-friendly home environment was estimated and its dynamics were profiled. The study was conducted in the Uyo Senatorial District of Akwa Ibom State. A multistage sampling procedure was adopted to select upper classes of elementary schools for data collection. Both descriptive and inferential statistics were deployed and results were obtained as follows. The majority of the respondents were male (51%) and were in late childhood and early adolescence with 12 years of age constituting 25.3% of the sample. The majority come from households with 2-5 persons (48.7%). The study showed that 86.3% of students were under parental guidance. A mixed-method research approach to item generation led to 12-item construct measures. The KMO and Bartlett's test affirmed the tenability of the measurement construct. However, the factor analytic results revealed four significant underlying dimensions of the factors for child creativity-friendly home environment programming. Incidence index analytics revealed relatively low occurrences and three incidence index magnitude categorizations among the twelve scaled items and the composite index analytics of the status of CCFHE revealed that 30.3% of the population are child creativity home environment friendly at a percentage index of 75.0 and above. The CCFHE background characteristics profile analysis indicated that out of 6 selected variables only 2 variables: age and guidance type had statistically significant variation CCFHE mean index. It suggests that most of the homes (69.7%) were not creative home environment friendly.